2023
DOI: 10.1038/s41467-023-38345-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of antibody immunity following Omicron BA.1 breakthrough infection

Abstract: Understanding the longitudinal dynamics of antibody immunity following heterologous SAR-CoV-2 breakthrough infection will inform the development of next-generation vaccines. Here, we track SARS-CoV-2 receptor binding domain (RBD)-specific antibody responses up to six months following Omicron BA.1 breakthrough infection in six mRNA-vaccinated individuals. Cross-reactive serum neutralizing antibody and memory B cell (MBC) responses decline by two- to four-fold through the study period. Breakthrough infection eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 37 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…Thus, although the immune response to the other partially cross-reacting viral strains was modest, it was able to powerfully boost the immune response to the priming viral strain, so maintaining a high level of immune response to the priming antigen for life, without a robust and lasting protective response against the new antigenic variants. This phenomenon has been repeatedly observed by different authors with influenza [100,101], other viruses [102], and more recently, even in the neutralizing antibody response to SARS-CoV-2 Omicron variant bivalent vaccine, which was not significantly higher than the one induced by the monovalent vaccine composed by the original Wuhan strain, associated with a lack of increase of T-cell response [98,[103][104][105][106][107][108]. A phenomenon similar to the "original antigenic sin" has even been described for cytotoxic T lymphocytes [109].…”
Section: Vaccinessupporting
confidence: 61%
“…Thus, although the immune response to the other partially cross-reacting viral strains was modest, it was able to powerfully boost the immune response to the priming viral strain, so maintaining a high level of immune response to the priming antigen for life, without a robust and lasting protective response against the new antigenic variants. This phenomenon has been repeatedly observed by different authors with influenza [100,101], other viruses [102], and more recently, even in the neutralizing antibody response to SARS-CoV-2 Omicron variant bivalent vaccine, which was not significantly higher than the one induced by the monovalent vaccine composed by the original Wuhan strain, associated with a lack of increase of T-cell response [98,[103][104][105][106][107][108]. A phenomenon similar to the "original antigenic sin" has even been described for cytotoxic T lymphocytes [109].…”
Section: Vaccinessupporting
confidence: 61%
“…We speculate this discrepancy might be largely due to the relatively longer interval (12 months) between breakthrough infection and the third CoronaVac ( 9 , 23 , 24 ). The long interval before Omicron breakthrough infection might preferentially recall cross-reactive antibodies that exhibit increased affinity and neutralization potency against Omicron, which could then drive a greater response given a subsequent antigen exposure ( 25 ). In addition, our finding aligns with recent evidence showing that either Omicron vaccination boosting or breakthrough infection not only triggers rapid memory cellular responses but also induces de novo B ( 26 ) and T cell ( 27 ) responses.…”
Section: Discussionmentioning
confidence: 99%
“…2A, Table S1). Also, several of the antibodies possessed features associated with convergent germlines or public clones (2,9), suggesting they may be representative of antibodies that can shape viral evolution. The selected antibodies possessed high reactivity to the RBD of the ancestral Wu-Hu-1 and varying degrees of cross-reactivity to other variants, with most having substantially reduced reactivity to Omicron BA.1 (BA.1) (4).…”
Section: Evolving Neutralizing Antibodies For Binding To Sars-cov-2 V...mentioning
confidence: 99%
“…S2). While it has been observed that affinity maturation generally increases antibody breadth and binding affinity to variants (2,15,16), it is conceivable that certain adaptations may produce local maxima that prevent further breadth.…”
Section: Evolving Neutralizing Antibodies For Binding To Sars-cov-2 V...mentioning
confidence: 99%
See 1 more Smart Citation